Traditional Medicine Programmes in Madagascar - Rasoanaivo, Philippe (World Bank, Washington, DC, 2012)
The note reviews Madagascar's inherited wealth of ethno-medical knowledge, being endowed with a flora of unique global importance on account of its biodiversity, endemicity, and ethno-medical uses. The government of Madagascar has shown its political commitment to traditional medicine by supporting, through an inter-ministerial convention, a commission to study regulations on traditional medicine, and its pharmacopoeia in the country, which was established in May 1996. The note further enumerates the general and operational objectives of the traditional medicine policy, and identifies associations and institutions involved in traditional medicine, in medicinal plant research and production, in pharmacopoeia, and in phyto-medicine production, and relevant programmes.